Psychometric Properties of the Chinese Version of the Clinically Useful Depression Outcome Scale for Patients with Major Depressive Disorder - Ma HY (Dove Medical Press, 2021)
Hai-Yan Ma,1,2 Xue-Mei Wang,1,2 Xiao-Jie Huang,2 Cheng-Jia Yang,2 Dong-Fang Sheng,2 Jing-Jing Yang,2 Ming-Zhi Xu2 1The Second School of Clinical Medicine, Southern Medical University, Guangzhou, Guangdong, People’s Republic of China; 2Guangdong Mental Health Center, Guangdong Provincial People’s Hospital, Guangdong Academy of Medical Sciences, Guangzhou, Guangdong, People’s Republic of ChinaCorrespondence: Ming-Zhi XuGuangdong Mental Health Center, Guangdong Provincial People’s Hospital, Guangdong Academy of Medical Sciences, No. 123 Huifu West Road, Guangzhou, 510120, Guangdong, People’s Republic of ChinaTel +86 81888553Fax +86 81862664Email mingzhixu@126.comObjective: This study aimed to evaluate the psychometric properties of the Chinese version of the Clinically Useful Depression Outcome Scale (CUDOS).Methods: One hundred ninety patients with major depressive disorder (MDD) according to Diagnostic and Statistical Manual of Mental Disorders, Fifth Edition (DSM-5) criteria were recruited to the study. The English version of the CUDOS was translated into Chinese using a forward and backward translation method, which was according to the guidelines of adaptation and validation of instruments in cross-cultural health care research. The Chinese version of the CUDOS, the 17-item Hamilton Rating Scale for Depression (HRSD) and the improved Clinical Global Impression-Severity Scale (iCGI-S) were used to evaluate depressive symptoms in one hundred ninety patients with MDD. One week after the first evaluation, sixteen patients were selected randomly for a second assessment. Reliability and validity tests and receiver operating characteristic curves were performed.Results: The internal consistency of the CUDOS was 0.95, and the split-half reliability coefficient of the CUDOS was 0.92. The correlation coefficient of the retest in sixteen patients was 0.77 (P < 0.01). There was a significant difference in the total score of the Chinese version of the CUDOS between the different levels of depression severity groups (P < 0.01). The ability of the CUDOS to identify patients in remission was high (area under ROC curve= 0.97). A cut-off score of 14/15 yielded 90.20% sensitivity and 93.60% specificity when iCGI-S=1.Conclusion: The Chinese version of the CUDOS is valuable as a brief and reliable instrument to assess depressive symptoms and clinical outcome. The findings suggest that the optimal cut-off score to identify patients in remission was 14/15.Keywords: MDD, the Chinese version of CUDOS, validity, reliability, cut-off score